P43 Using the HelpMeDoit! app and website to set and monitor weight loss goals and mobilise social support: qualitative findings. (September 2018) - Matthews, L; Pugmire, J; Simpson, S; Moore, L
Abstract : Background: HelpMeDoIt! is an app/website that harnesses social support for weight loss by enabling participants to nominate friends/family to help them with their weight loss goals. The intervention focused on goal setting, self-monitoring and social support, guided by elements of control theory, social cognitive theory, self-determination theory and social support theories. Objective: To explore the views and experiences of trial participants and their helpers and explore whether the intervention theory was supported. Methods: Qualitative interviews were conducted at 6 mth follow-up, via telephone, with intervention participants (n=22) and their helpers (n=9). The sample included individuals who had and had not engaged regularly with the app/website. Interviews were recorded, transcribed verbatim and analysed thematically. Results: Insights were gained on various aspects of the intervention, including: feasibility of using an app to set and monitor weight loss goals; the social support process; barriers to engagement; and suggested improvements for a future trial. Key findings indicated that participants and helpers engaged with the concept of the intervention but their participation was hindered to some extent by technical problems. Helpers often provided social support without using the app, e.g. face-to-face or by text. Findings supported several aspects of the intervention theory including: helpers providing instrumental, emotional and informational social support; increased knowledge and skills, sometimes via support from helpers e.g. cooking skills; increased action planning and problem solving via effective goal-setting; and increased motivation either via successful self-monitoring or goal accomplishment. Participant/helper insight provided several suggestions to enhance the intervention, including, providing a community of peer support. Conclusion: Participants were enthusiastic about having helpers to support them as well as using an app/website for lifestyle behaviour change. The technology needs to be free of technical issues to avoid unnecessary barriers to engagement. An effective weight loss intervention delivered via smartphone app/website has the potential for population-wide impact. Findings will be used to help inform a future full trial.